To Study the Role of Various Social Media Applications on Mental Health of Gen'Z in Ahmedabad City - Christian, Stuti; Vyas, Bhaskar; Vidani, Jignesh (MultiTech Publisher, 2024)
This study explores the role of social media applications on the mental health of Generation Z in Ahmedabad and their relationship to age and perception of the impact of social media on mood. Through quantification, the data that presented weak relationships was analysed between different hypotheses as all the hypotheses accepted the null hypothesis that presumes the age factor is not a determining influence on the perception of impacts wherein social media influences mental health. Overall, the results point towards a generational experience for Gen Z and indicate that variables such as unique personality characteristics and specific content interaction maybe even more meaningful than age in the relationship to technology. Implications of such studies extend further and connect with mental health professionals, educators, policymakers, or parents who need to understand the imperative to develop certain interventions or education that focus on fundamental digital literacy and the psychological impact of social media use. The longitudinal, qualitative experiences and types of content that might occur about potential impacts on mental health and emerging social media should be targeted by future research. This can also foster the thinking of the new generation who lives in such an advanced digital world.